The Begging Question : Sweden's Social Responses to the Roma Destitute - Hansson, Erik (Book collections on Project MUSE., 2023)
"The Begging Question examines Swedish society's reactions to the presence of begging EU citizens (mainly Romanian Roma people) in the years of 2014-16"--